The examination of the ProUni to improve the inclusive constitutional public policy by the Brazilian federal government - Gomes dos Anjos, Silvestre (Universidad Nacional del Litoral, 2020)
The object of this article is ProUni, as a permanent public policy, to include vacancies in higher education courses in private educational institutions, for underprivileged students, whose per capita income is low, exempt from tuition or with a substantial reduction in tuition. This scholarship program is aimed at the inclusive increase of the underprivileged population in higher education, having as a preponderant factor the use of the national exam, a kind of meritocracy. Through a bibliographic review on the topic, administrative and constitutional controls related to the execution of ProUni were addressed, with a view to its understanding. It is concluded that the knowledge and transparency of the mechanisms of entry into higher education through these types of scholarships are necessary tools for true administrative and social control, and may result in substantial improvements in this inclusive constitutional public policy under the responsibility of the Union.